Towards active exploration of static and dynamic scene geometry - Reid, I; Murray, D; Bradshaw, K (IEEE, 1994)
In this paper we describe the use of a steerable camera and active vision system in the real-time recovery of trajectories of objects moving on a planar surface in the scene. The system first self-calibrates the transformation from camera platform joint angles to scene plane coordinates by active observation of static scene geometry which has been stored as a model. The transformation is encoded as a homography. When distracted by motion, the camera saccades to the object and subsequently tracks it, and the 2D Cartesian components of the motion trajectory are recovered within the scene plane.